2003
DOI: 10.1164/rccm.200203-258oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Matrix Metalloproteinase Excess in Hospital-acquired Pneumonia

Abstract: In hospital-acquired pneumonia, extracellular matrix destruction is common and may be caused by excessive activity of matrix metalloproteinases (MMPs). Thirty patients with hospital-acquired pneumonia and 16 control subjects were studied. We evaluated the concentrations of MMP-8, MMP-9, and tissue inhibitor of metalloproteinase-1 in mini-bronchoalveolar lavage fluid (mini-BALF) and blood using zymography and specific immunoassays. In patients with hospital-acquired pneumonia concentrations of MMP-8 and MMP-9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
5
46
0
Order By: Relevance
“…We performed a zymographic analysis to determine active and inactive MMPs in the serums of CAP patients and controls. Active forms of MMP-2 and MMP-9 were 13 and 17 times higher, respectively, in CAP patients than controls, making our findings consistent with the results of previous studies (6,23,24,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We performed a zymographic analysis to determine active and inactive MMPs in the serums of CAP patients and controls. Active forms of MMP-2 and MMP-9 were 13 and 17 times higher, respectively, in CAP patients than controls, making our findings consistent with the results of previous studies (6,23,24,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, patients with severe pneumonia have higher MMP-2 levels and lower α-2 macroglobulin levels than nonsevere CAP patients, but the MMP-9 serum levels are the same. On the other hand, Hartog et al (24) reported higher MMP-8 and MMP-9 levels both in serum and mini-BAL fluid in HAP patients with a clinical pulmonary infection score (CPIS) of ≥7 than in patients with CPIS of <7, but no difference in TIMP-1 levels. The CPIS was originally proposed by Pugin et al (35,36) based on six variables (fever, leukocytosis, oxygenation, radiographic infiltrates, and tracheal aspirates and semiquantitative cultures of tracheal aspirates with Gram stain).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bacteria are frequently isolated from BAL in preschool wheezers and their presence is cited as being from upper respiratory tract contamination of the bronchoscope (33-37). TIMP-1 was reduced in these children, like adults with pneumonia (38), suggesting that bacteria are proinflammatory; however, other markers of inflammation like IL-8 were not increased in this group. If high TIMP-1 is associated with persistent wheezing, then the lower TIMP-1 concentrations in children with positive bacterial cultures may be a marker of protection in keeping with the hygiene hypothesis, where bacterial infection reduces the subsequent risk of allergic disease.…”
Section: Discussionmentioning
confidence: 63%